Marketyzacja usług publicznych (wybrane problemy) - Raszkowski, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The hereby article presents the concept of public services marketisation, i.e. public management by means of the implementation of market oriented mechanisms. Both, services and public goods, have been discussed. Different categories of public services were specified, as well as tasks carried out by public institutions in the field of meeting social needs. Certain problems of new public management model have also been touched upon. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 132-139